Job satisfaction and organizational commitment among academic staff in Kelantan - Nurul Nazwa Mohamed Aziz (2015)
This study attempts to maintain the relationship that exists between the different variables of job satisfaction and organizational commitment among academic staffs in some selected Public Universities in Kelantan. It also sets to determine if those related factors in organizational commitment can cause satisfaction among academics thereby impacting their academic excellence and to examine the factors influence the commitment of staffs.